One-step synthesis of flower-like Ag/AgCl/BiOCl composite with enhanced visible-light photocatalytic activity - Xiong, W.; Zhao, Q.; Li, Xin Yong; Zhang, D. (2011)
The flower-like Ag/AgCl/BiOCl composite was prepared by a one-step chemical bath method at low temperature for the first time. The morphology, crystallinity, composition, and optical property were well characterized by scanning electron microscope, X-ray diffraction, energy dispersive X-ray analysis, UV-vis diffuse reflectance spectrophotometer and nitrogen adsorption-desorption. The Ag/AgCl/BiOCl composite displayed enhanced visible-light photocatalytic activity against rhodamine B, which was much higher than Ag/AgCl or BiOCl. The mechanism for the degradation of rhodamine B over the Ag/AgCl/BiOCl was discussed. The superoxide radical and chlorine radical or the hole played critical roles instead of hydroxyl radicals. © 2011 Elsevier B.V. All rights reserved.